2012
DOI: 10.1017/s0007114511006830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D3in reducing metabolic and oxidative stress in the liver of streptozotocin-induced diabetic rats

Abstract: Diabetes mellitus is a growing health problem worldwide and is associated with severe liver complications. The aim of the present study is to analyse the status of metabolic and free-radical-scavenging enzymes and second messengers in the liver of streptozotocin (STZ)-induced diabetic rats, and to determine the hepatoprotective role of vitamin D 3 . All studies were performed using the liver of adult male Wistar rats. Gene expression studies were carried out using real-time PCR with specific probes. Second mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 59 publications
3
51
0
2
Order By: Relevance
“…Our results are consistent with previous reports that depicted the fact that hypovitaminosis D in adults may influence the risk of developing diabetes and metabolic syndrome [18,19]. A previous study has shown that Vitamin D levels are positively correlated with insulin sensitivity and negatively correlated with HbA1c levels, indicating Vitamin D deficiency as a predisposing factor in the pathogenesis of diabetes mellitus and cardiovascular diseases [20].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with previous reports that depicted the fact that hypovitaminosis D in adults may influence the risk of developing diabetes and metabolic syndrome [18,19]. A previous study has shown that Vitamin D levels are positively correlated with insulin sensitivity and negatively correlated with HbA1c levels, indicating Vitamin D deficiency as a predisposing factor in the pathogenesis of diabetes mellitus and cardiovascular diseases [20].…”
Section: Discussionsupporting
confidence: 93%
“…Proper mechanisms linking hypovitaminosis D with increased blood glucose level remains unclear, but there are some supporting studies which indicate that Vitamin D may directly affect pancreatic β-cell secretory functions through nuclear Vitamin D receptors and may affect the insulin sensitivity through insulin receptor expression regulation of intracellular receptors [10][11][12]. In a few animal studies, administration of calcitriol (activated form of Vitamin D) has been shown to prolong the onset of Type 1 Diabetes mellitus, mainly through immune regulation [19,31]. This is mainly because of effect of Vitamin D on inflammatory pathway [4,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La administración de vitamina D 2 y D 3 mostró niveles de glicemia significativamente menores en todos los grupos de experimentación en comparación al control positivo, concordando con los estudios realizados por George et al (15) , quienes demostraron que el tratamiento con vitamina D 3 restauró significativamente la homeostasis de la glucosa en la sangre en ratas diabéticas inducidas por estreptozotocina (STZ). Asimismo, Elseweidy et al (12) , en un estudio con un modelo de inducción de diabetes similar al nuestro, obtuvieron diferencias significativas en comparación a su grupo control positivo usando dosis de 170 UI/semana de vitamina D 3 .…”
Section: Discussionunclassified
“…At the end of incubation, antibody bound and free insulin were separated by the second antibody-polyethylene glycol aided separation method. Radioactivity associated with the bound fraction of sample and standards was measured to quantitate insulin concentration of samples [19].…”
Section: Estimation Of Blood Glucose and Circulating Insulin Levelsmentioning
confidence: 99%